COGNITIVE ANALYSIS OF INTERTEXTUALITY IN UZBEK AND ENGLISH POETRY - Nigina Davronova Akhmedjon kizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article will discuss the phenomenon of intertextuality from cognitive perspective. The samples from English and Uzbek poetry will be analyzed to illustrate cognitive features of intertextuality in literary discourse. As a common marker of intertextuality antonomasia will be analyzed in the samples and the other markers will enlisted.